Anti-Carbamylated Protein Antibody Test Accuracy In Some Iraqi Patients With Rheumatoid Arthritis - A Ali, Ghasak; S Abbas, Thanan (Medical Science Journal for Advance Research, 2022)
Background: Rheumatoid arthritis is a persistent, immune-mediated disorder that causes pain, edema, and inflammation in the joints. A genetic history that is high in risk, when paired with genomic markers and environmental exposures, triggers a series of actions that not only results in synovitis and arthritis, but also affects a great number of organs that are not related to the joints. The identification of novel autoantibodies playing key roles in different stages of disease remains an issue of interest for RA. Therefore, autoantibodies are necessary to assist in making a diagnosis and prediction more quickly in RA. Anti-Carbamylated Protein antibodies are a different class of anti- transformed protein antibody that is often found in the blood of RA patients. Objective: Rheumatoid arthritis has a recently discovered biomarker, which is an antibody called anti-carbamylated protein (CarP). Our aim is to evaluate the usefulness of anti-CarP as a diagnostic tool for RA. Participants and methods: The study conducted on 60 people diagnosed with RA as well as 60 people who served as healthy controls. Both the disease activity score (DAS28) and the health assessment questionnaire (HAQ) were evaluated. Estimates were made based on laboratory examinations such as ESR and rheumatoid factor (RF). Anti-CarP and Anti-CCP antibodies were measured by enzyme-linked immune-sorbent assay. Results:Anti-CarP levels were considerably higher in the patients with RA compared to the group that provided as a control (p > 0.000). Therefore, the sensitivity and specificity for anti-CarP antibodies were 39% and 98% respectively, while the sensitivity and specificity for anti-CCP antibodies were 83% and 95% respectively, and for RF were 68% and 83% respectively. The area under the curve (AUC) for anti-CarP antibodies was 0.67. Conclusions: Anti-CarP antibodies had comparatively lower sensitivity and slightly higher specificity than Anti-CCP.These findings suggest that anti-CarP antibodies works as an additional role in the diagnosis of RA.